Large Solutions for Semilinear Parabolic Equations Involving Some Special Classes of Nonlinearities - Constantin P. Niculescu; Ionel Rovenţa (Discrete Dynamics in Nature and Society)
We consider a new class of nonlinearities for which a nonlocal parabolic equation with Neumann boundary conditions has finite time blow-up solutions. Our approach is inspired by previous work done by Jazar and Kiwan (2008) and El Soufi et al. (2007).